CodiReal-PT: National Survey on Current Practices in Right Colon Oncological Surgery - Azevedo, José Gonçalves Moreira de; Sousa, Maria João Morais do Carmo Couto de; Cunha, Miguel Fernandes da Conceição; Fernandez, Laura Melina; Rama, Nuno José Gomes; Quintanilha, Rui Paulo de Medeiros (Journal of Coloproctology, 2024)
Introduction Colorectal cancer (CRC) is the third most prevalent tumor. Right colon cancer (RCC) comprises one-third of CRC cases and is associated with poorer outcomes, emphasizing the need for optimized treatment strategies. The present study aims to explore the nuances in the management of RCC across Portugal, focusing on surgical approaches and multidisciplinary treatment.Materials and Methods The CodiReal-PT was a cross-sectional survey-based study adhering to the guidelines of the Checklist for Reporting Results of Internet E-Surveys (CHERRIES), focusing on current practices in RCC oncological surgery. The survey comprised 31 questions divided into 4 sections (demographics, multidisciplinary approach, surgery practices regarding RCC, and postoperative management). It was made available via e-mail to all active members of the Portuguese Society of Surgery (Sociedade Portuguesa de Cirurgia, SPCIR, in Portuguese), and data collection lasted from November to December 2022.Results Data from 69% of Portuguese public hospitals was obtained. All the participant hospitals had multidisciplinary team meetings to manage CRC cases. However, 17% (n = 6) did not discuss all elective-setting cases during their meetings. Dedicated colorectal surgical teams were present in 86% (n = 31) of hospitals. Furthermore, the presence of these dedicated teams was associated with better practices, namely a higher volume of right colectomies (mean: 51.8 ± 32.6 versus 23.8 ± 4.8; p = 0.001), a preference for the laparoscopic approach (93.5 versus 60.0%; p = 0.021), and standardization of anastomotic techniques (83.9 versus 40.0%; p = 0.029).Conclusion The present nationwide survey-based study provides a comprehensive landscape of RCC management practices across Portugal, underscoring the significant role of dedicated colorectal surgical teams and the need for further practice standardization. Nevertheless, multidisciplinary team meetings in all surveyed hospitals are an important indicator of improved RCC care. Future research should focus on the impact of specific surgical techniques on oncological outcomes and the potential benefits of centralizing care to high-volume centers.
Keywords: Right Colon Cancer; oncologic Surgery; surgery; Portugal